A translational evaluation of potential iatrogenic effects of single and combined contingencies during functional analysis. Issue 1 (7th July 2019) - Retzlaff, Billie J.; Fisher, Wayne W.; Akers, Jessica S.; Greer, Brian D.
Abstract : Recent research suggests that combining putative reinforcers for problem behavior into a single, synthesized contingency may increase efficiency in identifying behavioral function relative to traditional functional analysis (FA). Other research suggests potential shortcomings of synthesized contingency analysis (SCA), such as the potential for false‐positive outcomes. In prior comparisons of traditional FAs and SCAs, investigators could not ascertain with certainty the true function(s) of the participants' problem behavior for use as the criterion variable. We conducted a translational study to circumvent this limitation by training a specific function for a surrogate destructive behavior prior to conducting a traditional FA and SCA. The traditional FA correctly identified the previously established function of the target response in all six cases and produced no iatrogenic effects. The SCA produced differentiated results in all cases and iatrogenic effects (i.e., an additional function) in three of six cases. We discuss these findings in terms of the mechanisms that may promote iatrogenic effects.